1971
DOI: 10.1017/s0043174500048219
|View full text |Cite
|
Sign up to set email alerts
|

Differential Phytotoxicity of Trifluralin and Nitralin

Abstract: Comparative phytotoxicity ofα,α,α-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine (trifluralin) and 4-(methylsulfonyl)-2,6-dinitro-N,N-dipropylaniline (nitralin) on several plant species indicated trifluralin was more toxic than nitralin to the shoots while nitralin was more toxic than trifluralin to the roots. An E0concentration, defined as that concentration required to prevent seedling emergence, was established for trifluralin on nearly all species assayed. Nitralin did not prevent emergence of any species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

1972
1972
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 9 publications
2
50
0
Order By: Relevance
“…In one study, cultured wheat roots were inhibited by herbicide concentrations of 0-02 ppm (Hess & Bayer, 1974), whereas Lund et al (1970 found that concentrations of 0-5-1-0 ppm were required to reduce the yield of cotton root tissue by 50%. Similariy, Barrentine & Warren (1971) reported that while 0-08 ppm nitralin halved the root growth of wheat and oat seedlings grown in sand culture, the herbicide needed to be applied at 0-74 ppm to have the same effect on soybean roots.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In one study, cultured wheat roots were inhibited by herbicide concentrations of 0-02 ppm (Hess & Bayer, 1974), whereas Lund et al (1970 found that concentrations of 0-5-1-0 ppm were required to reduce the yield of cotton root tissue by 50%. Similariy, Barrentine & Warren (1971) reported that while 0-08 ppm nitralin halved the root growth of wheat and oat seedlings grown in sand culture, the herbicide needed to be applied at 0-74 ppm to have the same effect on soybean roots.…”
Section: Introductionmentioning
confidence: 94%
“…As with other dinitroaniline herbicides, nitralin at low concentrations has a pronounced inhibitory effect on the development of roots and shoots. Barrentine & Warren (1971) reported that roots of many broadleaf and grass species, including the crop plants soybean (Glycine max 'Amsoy'), wheat (Triticum aestivum L. 'Dual Miller'), oats (Avena sativa L. 'Jaycee'), barley (Hordeum vulgare L. 'Harrison') and sorghum (Sorghum bicolor (L.) Moench 'RS-610'), and the roots of barnyardgrass (Echinochloa crus-galli (L.) Beauv.) and ivyleaf morning glory (Ipomoea hederacea (L.) Jacq.…”
Section: Introductionmentioning
confidence: 99%
“…Burnside (7) indicated that trifluralin residues persisted for one or more years, and Jacques and Harvey (13) reported that trifluralin residues could be detected 75 to 100 days after application to peas. Sorghum was shown to be one of the most sensitive crops to trifluralin residues (5). In this experiment, trifluralin residues reduced the stand of sorghum by about 44%, suggesting that the sorghum would not be a good double crop to follow peas treated with trifluralin.…”
Section: Discussionmentioning
confidence: 75%
“…Monocots are generally more susceptible than dicots [2] . Trifluralin remains localized in the area of contact [18,21] .…”
Section: Introductionmentioning
confidence: 96%